Approaching effects of the economic crisis on university efficiency: A comparative study of Germany and Italy - Erik E. Lehmann; Michele Meoli; Stefano Paleari; Sarah A. E. Stockinger (University of Augsburg, Chair of Management and Organization, 2017)
In this paper, we compare the efficiency of the Italian and German universities in the process of transforming public funding into the multiple outputs of a university, i.e. graduating students, publishing research, and patenting activity. We do this with a particular focus on the policies implemented following the financial crisis in 2008. Using a sample of 133 public universities, of which 73 public universities in Germany and 60 public universities in Italy observed over the period 2006-2011 we find that Italian universities perform significantly better in terms of output maximization than German universities. The crisis does not show a general impact, while the treatment effect indicates that Italian universities coped better during the crisis than their German counterparts at a highly significant level.
Keywords: H11; H12; I2; N30; 650; higher education; economic crisis; governance; data envelopment analysis; scale efficiency